Construction technologies of polymorphic network environment based on codesign of domain-specific software/hardware - Yuxiang HU; Zixi CUI; Ziyong LI; Yongji DONG; Pengshuai CUI; Jiangxing WU (Tongxin xuebao)
The deeply integration of information network and economic society has brought the trend of symbiotic coexistence, dynamic concurrency, evolution and revolution of network modals.Firstly, in order to satisfy the requirements of vertical industry applications, a scheme of the polymorphic network element based on codesign of domain-specific hardware/software was proposed, the key technologies to construct polymorphic network environment were discussed as well.Then, to solve the resource competition problem between diversified network modals, a heterogeneous resource allocation and replacement method was proposed by integration of computing, storage and forwarding, which dynamically adjusted the resource-allocation strategy according to the traffic volume to realize the efficient resource utilization.Experimental results show that the proposed scheme can provide the basic platform support for the construction of polymorphic network by separation of technical systems and supporting environment.